[Rezension von: Stoeckl, Kristina, 1977-, The moralist international : Russia in the global culture wars] - Knox, Zoe Katrina (A journal of church and state, 2024)
Since Patriarch Kirill’s notorious speech on March 6, 2022, which justified Russia’s full-scale invasion of Ukraine 11 days prior, analysts have questioned